Auto-steering based precise coordination method for in-field multi-operation of farm machinery - Wang, Jie; Zhu, Yuting; Chen, Zhibo; Yang, Lili; Wu, Caicong (International Journal of Agricultural and Biological Engineering, 2018)
Multi-operation within a field and multi-machinery within a machinery operation are common in the scene of scaled farm machinery service, especially with soaring usage of automated steering system in small and medium machinery cooperatives. The object of this study was to explore a precise and efficient in-field coordination method to realize flow-shop scheduling for farm machinery fleet equipped with RTK-GNSS based auto-steering system. The new method is based on three-dimensional coordinate system (XYZ), within which the concept of field, operation strip, and operation task were defined. Under this concept framework, the operation strip state was further defined and its updating algorithm was designed, which can be used for optimization simulations and experiments. To evaluate the method, the waiting time between simulation and a real-world case was compared, and one cloud based prototype system was developed to demonstrate the practicability in the field by using NX200+ automated steering system. The simulations showed that the in-field coordination can shorten the waiting time between two adjacent operations. The waiting time between rotary hoeing and seeding can be shortened from 4 h to 6.3 min. The field experiment showed that the prototype system could keep good consistency of ridges for a fleet by sharing the guidance line.Keywords: GNSS, auto-steering system, in-field coordination operation, farm machinery, method, simulationDOI: 10.25165/j.ijabe.20181105.3827Citation: Wang J, Zhu Y T, Chen Z B, Yang L L, Wu C C. Auto-steering based precise coordination method for in-field multi-operation of farm machinery. Int J Agric & Biol Eng, 2018; 11(5): 174–181.